The Mediating Role Of Business Performance In The Relationship Between Financial Literacy And Business Sustainability Among MSMES In Malang Indonesia - Sabna Ainazah Fatikhah; Yanuar Trisnowati; Ruhil Arwani Husein (Jurnal Manajerial, 2026)
Background – This study investigates the relationship between financial literacy and business sustainability among Micro, Small, and Medium Enterprises (MSMEs) in Malang Regency/City, emphasizing the mediating role of business performance. The research aims to uncover how financial literacy affects operational decisions and outcomes, offering practical insights for improving long-term sustainability. Aim – This study aims to explain in detail the effect of financial literacy on MSME sustainability, while considering the mediating role of business performance. The focus is to identify the extent to which financial knowledge influences operational efficiency and the long-term resilience of businesses. Design / methodology / approach – A quantitative method was used with a sample of 300 MSMEs that have operated for at least one year. Using simple random sampling, data were collected and analysed with Structural Equation Modelling-Partial Least Squares (SEM-PLS). Findings – The results indicate that financial literacy has a positive and statistically significant effect on MSME business performance (β = 0.471; t = 8.708; p < 0.001). Financial literacy also shows a direct positive effect on business sustainability (β = 0.201; t = 3.536; p < 0.001), while business performance demonstrates a stronger direct influence on sustainability (β = 0.567; t = 12.719; p < 0.001). The model explains 22.1% of the variance in business performance and 46.9% of the variance in sustainability, indicating acceptable explanatory power. These findings confirm that business performance acts as a critical mediating mechanism through which financial literacy enhances business sustainability, suggesting that improving entrepreneurs’ financial capabilities contributes both directly and indirectly to sustainable MSME development. Conclusion – The conclusion obtained in this study is that financial literacy has a positive and statistically significant effect on MSME business performance, financial literacy has a direct positive effect on business sustainability, and business performance has a critical mediating role between financial literacy and business sustainability Research implication – The results show that financial literacy significantly improves MSME performance (β = 0.471; p < 0.001) and sustainability (β = 0.201; p < 0.001), while performance strongly drives sustainability (β = 0.567; p < 0.001). These empirical patterns indicate that financial education initiatives should be prioritized because they improve performance first, which then strengthens sustainability. Policymakers are therefore encouraged to design targeted, practical financial programs linked to performance coaching. Limitations – The study is limited to the Malang region and uses a quantitative design. It focuses on three variables, excluding factors like access to financing, government support, technology, and market dynamics.